Prove this

Let ϕ\phi denote the golden ratio, ϕ=1+52\phi = \dfrac{1+\sqrt5}2 , prove that ϕ138=n=0(1)n+1(2n+1)!(n+2)!n!42n+3.\phi -\frac { 13 }{ 8 } =\displaystyle\sum _{ n=0 }^{ \infty }{ \frac { (-1)^{ n+1 }(2n+1)! }{ (n+2)!n!{ 4 }^{ 2n+3 } } } .

#Calculus

Note by Hamza A
5 years, 4 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Lemma :

If f(a)=r=0(1)rΓ(r+32)4r(r+a)Γ(r+1)\displaystyle f(a) = \sum_{r=0}^{\infty} (-1)^{r} \dfrac{\Gamma\left(r+\frac{3}{2}\right)}{4^r(r+a)\Gamma(r+1)}

Then f(1)f(2)=π2(721605)\displaystyle f(1) - f(2) = \dfrac{\sqrt{\pi}}{2} \left(72 - \dfrac{160}{\sqrt{5}}\right)

Proof :

Using Infinite Binomial Series,

(1+x)n=r=0(1)rΓ(n+r)Γ(n)Γ(r+1)xr\displaystyle (1+x)^{-n} = \sum_{r=0}^{\infty} (-1)^{r} \dfrac{\Gamma(n+r)}{\Gamma(n)\Gamma(r+1)} x^r

Putting n=32\displaystyle n = \dfrac{3}{2} and noting that 1z+1=01xzdx \displaystyle \dfrac{1}{z+1} = \int_{0}^{1} x^z \mathrm{d}x, we have,

f(1)f(2)=Γ(32)01(1x)(1+x4)32dx\displaystyle f(1) - f(2) = \Gamma\left(\dfrac{3}{2}\right) \int_{0}^{1} (1-x) \left(1+\dfrac{x}{4}\right)^{-\frac{3}{2}} \mathrm{d}x

=π2[16(x+8)x+4]01(Γ(32)=π2)\displaystyle = \dfrac{\sqrt{\pi}}{2}\left[\dfrac{-16(x+8)}{\sqrt{x+4}}\right]_{0}^{1} \qquad \left( \because \Gamma \left(\frac{3}{2}\right) = \dfrac{\sqrt{\pi}}{2} \right)

=π2(721605)\displaystyle = \dfrac{\sqrt{\pi}}{2} \left(72 - \dfrac{160}{\sqrt{5}}\right)

This proves the Lemma.

Now, the series can be written as,

S=r=0(1)r+1Γ(2r+2)42r+3Γ(r+3)Γ(r+1)\displaystyle \text{S} = \sum_{r=0}^{\infty} (-1)^{r+1} \dfrac{ \Gamma(2r+2)}{4^{2r+3} \Gamma(r+3)\Gamma(r+1)}

Using Gamma Duplication Formula, we have,

S=125πr=0(1)rΓ(r+32)4rΓ(r+3)\displaystyle \text{S} = -\dfrac{1}{2^5 \sqrt{\pi}} \sum_{r=0}^{\infty} (-1)^{r} \dfrac{\Gamma(r+\frac{3}{2})}{4^r \Gamma(r+3)}

=125πr=0(1)rΓ(r+32)4r(r+1)(r+2)Γ(r+1)\displaystyle = -\dfrac{1}{2^5 \sqrt{\pi}} \sum_{r=0}^{\infty} (-1)^{r} \dfrac{ \Gamma(r+\frac{3}{2})}{4^r (r+1)(r+2) \Gamma(r+1)}

=125π[r=0(1)rΓ(r+32)4r(r+1)Γ(r+1)r=0(1)rΓ(r+32)4r(r+2)Γ(r+1)]\displaystyle = -\dfrac{1}{2^5 \sqrt{\pi}} \left[\sum_{r=0}^{\infty} (-1)^{r} \dfrac{ \Gamma(r+\frac{3}{2})}{4^r (r+1) \Gamma(r+1)} -\sum_{r=0}^{\infty} (-1)^{r} \dfrac{\Gamma(r+\frac{3}{2})}{4^r (r+2) \Gamma(r+1)} \right]

Using the Lemma,

S=125π(f(1)f(2))=125π(π2(721605))\displaystyle \text{S} = -\dfrac{1}{2^5 \sqrt{\pi}} \left(f(1) - f(2)\right) = -\dfrac{1}{2^5 \sqrt{\pi}} \left(\dfrac{\sqrt{\pi}}{2} \left(72 - \dfrac{160}{\sqrt{5}}\right)\right)

Simplifying, we have,

S=ϕ138\displaystyle \boxed{\text{S} = \phi -\dfrac{13}{8}}

Ishan Singh - 5 years, 3 months ago

Log in to reply

@Hummus a Try this. Little similar to your question.

Ishan Singh - 5 years, 3 months ago

@Ishan Singh

you're the best at these problems :)

Hamza A - 5 years, 3 months ago
×

Problem Loading...

Note Loading...

Set Loading...